2018
DOI: 10.3389/fendo.2018.00009
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Cord Blood Vitamin D Status and Anthropometric Measurements in Term Newborns at Birth

Abstract: IntroductionVitamin D deficiency in pregnant women may result in reduced neonatal development due to the fact that systemic vitamin D status during fetal life depends on maternal concentrations. Some authors reported significant differences in neonatal anthropometric measurements depending on maternal vitamin D concentrations.ObjectiveThe aim of this study is to evaluate the relationship between maternal and cord blood concentrations of vitamin D and neonatal anthropometric measurements at birth.Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 37 publications
9
30
0
Order By: Relevance
“…The positive association between vitamin D intake from food and supplements and maternal VDD is in agreement with some [34,41,[43][44][45][46][47][48], but not all [39] of the previous studies. It appears that vitamin D intake from food and supplements contributed signi cantly to 25OHD level in population, in which sun exposure is minimum or dermal synthesis of 25OHD is limited.…”
Section: Discussionsupporting
confidence: 91%
“…The positive association between vitamin D intake from food and supplements and maternal VDD is in agreement with some [34,41,[43][44][45][46][47][48], but not all [39] of the previous studies. It appears that vitamin D intake from food and supplements contributed signi cantly to 25OHD level in population, in which sun exposure is minimum or dermal synthesis of 25OHD is limited.…”
Section: Discussionsupporting
confidence: 91%
“…The positive association between vitamin D intake from food and supplements and maternal VDD is in agreement with most of the previous ndings [39,46,[49][50][51][52][53][54]] except a study [44]. It was found that vitamin D intake from foods and supplements contributed signi cantly to 25OHD level in population exposure to sun is minimum or dermal synthesis of 25OHD is limited.…”
Section: Vddsupporting
confidence: 90%
“…Additionally, the percentage that met criteria for vitamin D deficiency (23%) or insufficiency (27%) were much lower than in other populations where the majority met these criteria (Table S5). The higher mean 25(OH)D could be due to higher ultraviolet indexes and/or exposure in this California population or fortification of vitamin D in several foods within the United States; previous studies have shown similarly higher umbilical cord blood serum 25(OH)D3 (59–67 nmol/L) in United States Caucasians (from Ohio and Pennsylvania) [Bodnar et al, ; Seto et al, ] compared to Europeans (17–67 nmol/L) [Delvin, Salle, Glorieux, Adeleine, & David, ; Pludowski et al, ; Wierzejska et al, ].…”
Section: Discussionmentioning
confidence: 92%